Floral scent and species divergence in a pair of sexually deceptive orchids. Issue 15 (28th June 2017) - Gervasi, Daniel D. L.; Selosse, Marc‐Andre; Sauve, Mathieu; Francke, Wittko; Vereecken, Nicolas J.; Cozzolino, Salvatore; Schiestl, Florian P.
Abstract: Speciation is typically accompanied by the formation of isolation barriers between lineages. Commonly, reproductive barriers are separated into pre‐ and post‐zygotic mechanisms that can evolve with different speed. In this study, we measured the strength of different reproductive barriers in two closely related, sympatric orchids of the Ophrys insectifera group, namely Ophrys insectifera and Ophrys aymoninii to infer possible mechanisms of speciation. We quantified pre‐ and post‐pollination barriers through observation of pollen flow, by performing artificial inter‐ and intraspecific crosses and analyzing scent bouquets. Additionally, we investigated differences in mycorrhizal fungi as a potential extrinsic factor of post‐zygotic isolation. Our results show that floral isolation mediated by the attraction of different pollinators acts apparently as the sole reproductive barrier between the two orchid species, with later‐acting intrinsic barriers seemingly absent. Also, the two orchids share most of their fungal mycorrhizal partners in sympatry, suggesting little or no importance of mycorrhizal symbiosis in reproductive isolation. Key traits underlying floral isolation were two alkenes and wax ester, present predominantly in the floral scent of O. aymoninii . These compounds, when applied to flowers of O. insectifera, triggered attraction and a copulation attempt of the bee pollinator of O. aymoninii and thus led to the (partial) breakdown of floral isolation. Based on our results, we suggest that adaptation to different pollinators, mediated by floral scent, underlies species isolation in this plant group. Pollinator switches may be promoted by low pollination success of individuals in dense patches of plants, an assumption that we also confirmed in our study. Abstract : In this article, we provide a detailed analysis of reproductive isolation in a species‐pair of sexually deceptive orchids. We show experimentally that floral isolation, mediated by production of different floral scent compounds, is the major mechanism of reproductive isolation, and indicate a potential mechanism driving adaptation to new pollinators.